2000
DOI: 10.1016/s0304-4157(00)00010-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of membrane proteins and lipids with solubilizing detergents

Abstract: Detergents are indispensable in the isolation of integral membrane proteins from biological membranes to study their intrinsic structural and functional properties. Solubilization involves a number of intermediary states that can be studied by a variety of physicochemical and kinetic methods; it usually starts by destabilization of the lipid component of the membranes, a process that is accompanied by a transition of detergent binding by the membrane from a noncooperative to a cooperative interaction already b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
734
3
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 910 publications
(795 citation statements)
references
References 198 publications
35
734
3
6
Order By: Relevance
“…The development of a rational approach to the solubilization of membrane proteins always requires a review of the literature to determine the detergent type and the conditions that are generally used for the solubilization of the protein of interest (1,(3)(4)(5)(6)(7)(8)10). All assays were carried at 37ºC as described in Methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of a rational approach to the solubilization of membrane proteins always requires a review of the literature to determine the detergent type and the conditions that are generally used for the solubilization of the protein of interest (1,(3)(4)(5)(6)(7)(8)10). All assays were carried at 37ºC as described in Methods.…”
Section: Discussionmentioning
confidence: 99%
“…Several excellent reviews can be found on detergents, their physical properties and their use in the solubilization of membrane proteins (1)(2)(3)(4). Due to three important factors, non-ionic detergents are frequently used for the solubilization of protein membranes: i) their efficiency in breaking the lipid-lipid and lipid-protein interactions, ii) their inefficiency in weakening protein-protein interactions, and iii) their property of being less denaturing than the ionic detergents (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…However, this trajectory is just a suggestion, as it is difficult to follow each peak unambiguously. (33,34,51)). Line broadening can be seen at intermediate detergent concentrations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our study focuses on TRP3 accommodation at the hydrophilic/ hydrophobic interface of micelles and subsequent events. The structure and dynamics of TRP3 were examined in the presence of micelles of different chemical nature: zwitterionic (lysolauroylphosphatidylcholine 1-lauroyl-2-hydroxy-sn-glycero-3-phosphocholine (LLPC), n-dodecylphosphocholine (DPC), and N-dodecyl-N,N-(dimethylammonio) butyrate (DDMAB), anionic 1-myristoyl-2-hydroxy-sn-glycero-3-phospho-(1 0 -rac-glycerol) (LMPG), and nonionic (octylglucoside (OG)) (23,24,(31)(32)(33)(34)(35). The conformational ensemble was evaluated during detergent titration and it was found that the peptide interacts via conformational selection.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Figure 2, the active surfaces of the labwares become saturated by the CHAPS monomers, and once the sample is introduced in the sampling bottle, the analytes are available for extraction. Additionally, it was observed that for 12 complete elimination of adsorption losses from the 96-well plate, a concentration above the critical micelle concentration (CMC, 3-10 mM 14 ) is important, particularly for the most non polar compounds in the study. This also shows that CHAPS is not only saturating the lab-ware surfaces, it is also able to stabilize the analytes in the micelles/sample (Figure 2).…”
Section: Theoretical Consideration Of Micellar Spme and Micelle Assismentioning
confidence: 99%